An automatized methodology to generate velocity distortion panels for wind tunnel testing. Issue 227 (August 2022) - Broatch, A.; Margot, X.; García-Tíscar, J.; Felgueroso, A.
Abstract: Replicating the actual velocity distribution that a target will experience in real life is sometimes necessary to perform realistic aerodynamic characterizations in wind tunnels. In industrial aerodynamics, this is especially critical in aeroengine inlets, automotive and aircraft compressors, atmospheric boundary layers, etc. However, wind tunnels are designed to provide a flow as uniform as possible. To reproduce the desired velocity distribution, the utilization of certain devices for flow adaption is typically required, in a trial-and-error procedure. In this research, we propose a methodology to automatically generate distortion screens to reproduce a desired target velocity distribution, based on analytical relations between the porosity in a media and the total pressure loss induced by this porosity. A numerical routine is used to design a robust and easily-manufactured hexahedral grid that matches the required porosity distribution. Once this geometry is generated, it can be realized by means of widely-available, inexpensive additive manufacturing. To validate the proposed methodology, two geometries that reproduce 1D velocity distributions and another geometry which considers a bi-dimensional distribution have been generated and studied using both computational fluid dynamics and wind tunnel measurements, demonstrating good agreement between the target velocity distributions and those obtained numerically and experimentally. Highlights: Flow distortion is often required in wind tunnels to reproduce inflow conditions. Typically, velocity distributions are achieved by a trial-and-error processes. An automated semi-analytical methodology is proposed to address this issue. The procedure generates robust, 3D-printable hexahedral panel geometries. Three 1D and 2D distortion panels are numerically and experimentally validated.